A New Construction of Multisender Authentication Codes from Polynomials over Finite Fields - Xiuli Wang (Journal of Applied Mathematics)
Multisender authentication codes allow a group of senders to construct an authenticated message for a receiver such that the receiver can verify the authenticity of the received message. In this paper, we construct one multisender authentication code from polynomials over finite fields. Some parameters and the probabilities of deceptions of this code are also computed.